Exports and Distance in a Digitalized World: Gravity Model Applied to the Indian Exports of Software - P.K.M. Tharakan and I. Van Beveren
In this study we apply the gravity model to the fast growing Indian exports of software and to the much more slowly growing total Indian commodity exports. In analyzing the results obtained, we pay special attention to the distance variable, linguistic connections, and trade facilitating networks. The insights gained from our analysis might be relevant in appraising the prospects of the new wave of emerging country exporters of software. Further, the lack of importance of distance as a trade resistance variable in software (which we confirm in our study) has interesting implications for trade liberalization in, and spatial agglomeration of, some industries